2017
DOI: 10.1007/s11356-017-0458-4
|View full text |Cite
|
Sign up to set email alerts
|

210Po and 210Pb bioaccumulation and possible related dose assessment in parasol mushroom (Macrolepiota procera)

Abstract: Presented are results of a study on accumulation and distribution of 210Po and 210Pb in the fruitbodies of parasol mushroom (Macrolepiota procera) and risk to human consumer due to exposure from highly radiotoxic decay particles emitted by both radionuclides. Mushrooms were collected from 16 forested places in central and northern regions of Poland. Activity concentrations of 210Po and 210Pb were determined after radiochemical separation of nuclides and subsequent measurement using validated method and alpha s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Although Guillén and Baeza ( 2014 ) stated the most important feature in polonium accumulation in mushrooms was its species, our results confirmed previous observations (confirmed by inter-species studies)—the most important aspects in 210 Po and 210 Pb distribution are local climate and geological conditions, e.g., atmospheric fallout, geological structure, natural radioactivity (Vaaramaa et al 2009 ; Gwynn et al 2013 ; Strumińska-Parulska et al 2016 ; Strumińska-Parulska and Olszewski 2018 ; Szymańska et al 2018 ). Besides, in the forest area, the trees might decrease the influence of wet and dry deposition on soils and mushrooms (Kirchner and Daillant 1998 ; Strumińska-Parulska et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although Guillén and Baeza ( 2014 ) stated the most important feature in polonium accumulation in mushrooms was its species, our results confirmed previous observations (confirmed by inter-species studies)—the most important aspects in 210 Po and 210 Pb distribution are local climate and geological conditions, e.g., atmospheric fallout, geological structure, natural radioactivity (Vaaramaa et al 2009 ; Gwynn et al 2013 ; Strumińska-Parulska et al 2016 ; Strumińska-Parulska and Olszewski 2018 ; Szymańska et al 2018 ). Besides, in the forest area, the trees might decrease the influence of wet and dry deposition on soils and mushrooms (Kirchner and Daillant 1998 ; Strumińska-Parulska et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The L. pseudoscabrum due to the BCF values below unity (BCF < 1) is considered as excluder of 210 Po and 210 Pb, similarly to other mushrooms studied so far such as Leccinum sp. and parasol mushroom ( Macrolepiota procera ) (Strumińska-Parulska et al 2016 , 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be clear, the lack of statistical difference between both groups is probably related to a small sample size (number of people eating much more seafood products than statistical amount). Some previous studies showed there are some food products estimated as insignificant, that might be an important source of 210 Po and 210 Pb [61][62][63][64][65][66]. The activity concentrations of 210 Pb for analyzed groups were in the range of 1.40 ± 0.11 and 49.6 ± 1.48 Bq kg −1 dry wt.…”
Section: Fish Consumptionmentioning
confidence: 88%